A cyclo‐P6 Ligand Complex for the Formation of Planar 2D Layers. Issue 8 (19th January 2016) - Heindl, Claudia; Peresypkina, Eugenia V.; Lüdeker, David; Brunklaus, Gunther; Virovets, Alexander V.; Scheer, Manfred
Abstract: The all‐phosphorus analogue of benzene, stabilized as middle deck in triple‐decker complexes, is a promising building block for the formation of graphene‐like sheet structures. The reaction of [(CpMo)2 (μ, η 6 :η 6 ‐P6 )] (1 ) with CuX (X=Br, I) leads to self‐assembly into unprecedented 2D networks of [(CpMo)2 P6 (CuBr)4 ] n (2 ) and [(CpMo)2 P6 (CuI)2 ] n (3 ). X‐ray structural analyses show a unique deformation of the previously planar cyclo ‐P6 ligand. This includes bending of one P atom in an envelope conformation as well as a bisallylic distortion. Despite this, 2 and3 form planar layers. Both polymers were furthermore analyzed by 31 P 1 H magic angle spinning (MAS) NMR spectroscopy, revealing signals corresponding to six non‐equivalent phosphorus sites. A peak assignment is achieved by 2D correlation spectra as well as by DFT chemical shift computations. Abstract : The triple‐decker complex [(CpMo)2 (μ, η 6 :η 6 ‐P6 )] forms with CuX (X=Br, I) novel two‐dimensional planar networks that resemble graphene‐like sheets. A unique distortion of the hexaphosphabenzene ligand occurs during this process. The polymers were characterized by X‐ray structural analysis, 1D and 2D 31 P 1 H MAS NMR spectroscopy, and also DFT chemical shift computations.